THE ROLE OF PARADOX IN MARY SHELLEY’S FRANKENSTEIN PERAN PARADOKS DALAM FRANKENSTEIN OLEH MARY SHELLEY - Latief , Abdul; Herlambang, Diaz Billy; Putri, Kayla Rania; Nurholis, Nurholis (Cahaya Ilmu Bangsa Institute, 2025)
Mary Shelley’s Frankenstein is a piece of Gothic literature which has lasted in popularity until the modern age. There are numerous interesting aspects to analyze from this book. One such aspect is the use of paradoxes in this novel and its execution in the story. This paper aims to analyze four types of paradoxes present in Mary Shelley's novel Frankenstein: Situational Paradox, Verbal Paradox, Character Paradox, and Thematic Paradox. The Situational Paradox highlights the contradictions between the intentions of Victor Frankenstein and the disastrous outcomes of his experiments. The Verbal Paradox examines instances of language that convey conflicting meanings, reflecting the complexity of the characters' experiences. The Character Paradox explores the duality within the characters, particularly in Victor and his creation, as they navigate their desires and identities. Finally, the Thematic Paradox addresses the broader moral and ethical dilemmas presented in the novel, showcasing the conflicts between ambition, responsibility, and the nature of humanity. This study will approach these issues from a mainly posmodern point of view which explores the complexity of these paradoxes. The results of this analysis revealed new insights into how these paradoxes not only serve as narrative elements but also reflect the ethical and philosophical dilemmas of the era. It can be concluded that Shelley employs paradoxes in various forms situational, character, verbal, and thematic-to highlight the complexities of her narrative and deepen the understanding of her characters and themes. Frankenstein oleh Mary Shelley adalah karya sastra Gotik yang tetap populer hingga zaman modern. Ada banyak aspek menarik yang dapat dianalisis dari buku ini. Salah satu aspek tersebut adalah penggunaan paradoks dalam novel ini dan pelaksanaannya dalam cerita. Makalah ini bertujuan untuk menganalisis empat jenis paradoks yang ada dalam novel Frankenstein karya Mary Shelley: Paradoks Situasional, Paradoks Verbal, Paradoks Karakter, dan Paradoks Tematik. Paradoks Situasional menyoroti kontradiksi antara niat Victor Frankenstein dan hasil eksperimennya yang membawa bencana. Paradoks Verbal meneliti contoh-contoh bahasa yang menyampaikan makna yang saling bertentangan, yang mencerminkan kompleksitas pengalaman para tokoh. Paradoks Karakter mengeksplorasi dualitas dalam diri para tokoh, khususnya dalam diri Victor dan ciptaannya, saat mereka menavigasi keinginan dan identitas mereka. Terakhir, Paradoks Tematik membahas dilema moral dan etika yang lebih luas yang disajikan dalam novel, yang memperlihatkan konflik antara ambisi, tanggung jawab, dan sifat manusia. Studi ini akan membahas isu-isu tersebut dari sudut pandang posmodern yang mengeksplorasi kompleksitas paradoks tersebut. Hasil analisis ini mengungkapkan wawasan baru tentang bagaimana paradoks tersebut tidak hanya berfungsi sebagai elemen naratif tetapi juga mencerminkan dilema etika dan filosofis pada era tersebut. Dapat disimpulkan bahwa Shelley menggunakan paradoks dalam berbagai bentuk situasional, karakter, verbal, dan tematik untuk menyoroti kompleksitas narasinya dan memperdalam pemahaman karakter dan temanya.